Prevalence of karyotype alterations in couples with recurrent pregnancy loss in a tertiary center in Brazil - Elaine Cristina Fontes de Oliveira; Ines Katerina Damasceno Cavallo Cruzeiro; Cezar Antônio Abreu de Souza; Fernando Marcos Reis (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective To assess the prevalence and type of chromosomal abnormalities in Brazilian couples with recurrent pregnancy loss (RPL) and compare the clinical characteristics of couples with and without chromosome abnormalities. Methods We assessed the medical records of 127 couples with a history of two or more miscarriages, referred to a tertiary academic hospital in Belo Horizonte, Brazil, from January 2014 to May 2023. Karyotype was generated from peripheral blood lymphocyte cultures, and cytogenetic analysis was performed according to standard protocols by heat-denatured Giemsa (RHG) banding. Results Abnormal karyotypes were detected in 10 couples (7.8%). The prevalence of chromosomal abnormalities was higher among females (6.3%) compared to males (2.0%), but this difference was not statistically significant (p=0.192). The mean number of miscarriages was. 3.3 ± 1.1 in couples with chromosome abnormalities and 3.1 ± 1.5 in couples without chromosome abnormalities (p=0.681). Numerical chromosomal anomalies (6 cases) were more frequent than structural anomalies. Four women presented low-grade Turner mosaicism. No differences were found between couples with and without karyotype alterations, except for maternal age, which was higher in the group with chromosome alterations. Conclusion The prevalence of parental chromosomal alterations in our study was higher than in most series described in the literature and was associated with increased maternal age. These findings suggest that karyotyping should be part of the investigation for Brazilian couples with RPL, as identifying the genetic etiology may have implications for subsequent pregnancies.